“A 16-yr Follow-up of the European Randomized study of Screening for Prostate Cancer” - Hugosson, Jonas (Eur Urol, 2019)
BACKGROUND: The European Randomized study of Screening for Prostate Cancer (ERSPC) has previously demonstrated that prostate-specific antigen (PSA) screening decreases prostate cancer (PCa) mortality. OBJECTIVE: To determine whether PSA screening decreases PCa mortality for up to 16 yr and to assess results following adjustment for nonparticipation and the number of screening rounds attended. DESIGN, SETTING, AND PARTICIPANTS: This multicentre population-based randomised screening trial was conducted in eight European countries. Report includes 182 160 men, followed up until 2014 (maximum of 16 yr), with a predefined core age group of 162 389 men (55–69 yr), selected from population registry. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: The outcome was PCa mortality, also assessed with adjustment for nonparticipation and the number of screening rounds attended. RESULTS AND LIMITATIONS: The rate ratio of PCa mortality was 0.80 (95% confidence interval [CI] 0.72–0.89, p < 0.001) at 16 yr. The difference in absolute PCa mortality increased from 0.14% at 13 yr to 0.18% at 16 yr. The number of screening invitations needed to prevent one PCa death was 570 at 16 yr compared with 742 at 13 yr. The number needed to diagnose was reduced to 18 from 26 at 13 yr. Men with PCa detected during the first round had a higher prevalence of PSA >20 ng/ml (9.9% compared with 4.1% in the second round, p < 0.001) and higher PCa mortality (hazard ratio = 1.86, p < 0.001) than those detected subsequently. CONCLUSIONS: Findings corroborate earlier results that PSA screening significantly reduces PCa mortality, showing larger absolute benefit with longer follow-up and a reduction in excess incidence. Repeated screening may be important to reduce PCa mortality on a population level. PATIENT SUMMARY: In this report, we looked at the outcomes from prostate cancer in a large European population. We found that repeated screening reduces the risk of dying from prostate cancer.